Implementation of Job Analysis Results in Fulfilling Public Service Standards at the Education and Culture Service in West Sumbawa Regency - Nasruddin, Nasruddin; Suparman, Suparman; Najamuddin, Najamuddin (Lembaga Penelitian dan Pendidikan Mandala, 2023)
Fulfillment of public service standards is an aspect that must be met in maintaining the quality of services provided by each government agency. In this context, the Education and Culture Office in West Sumbawa Regency, the implementation of the results of the position analysis has an important role in efforts to improve the quality of public services. This study aims to reveal how the results of the position analysis can be used in fulfilling public service standards at the Education and Culture Office in West Sumbawa Regency. This study used qualitative methods by collecting data through interviews, document studies, and observations. The results showed that the results of the position analysis have provided a clear view of the duties, responsibilities, and qualifications required by each position in the West Sumbawa Regency Education and Culture Office. Periodic performance evaluations are used to ensure public services continue to meet established standards; 5) Preparation of Service Standards, the results of position analysis are used as a basis for compiling clear public service standards. So that it can help in providing firm guidelines for employees in providing services to the community.This study concludes that the implementation of the results of the position analysis is very important in meeting public service standards at the Education and Culture Office in West Sumbawa Regency. With a better understanding of the duties and loyal responsibilities of office holders, it can improve the efficiency, competence, and quality of services provided to the community. This contributes positively in increasing public satisfaction with public services provided by the head of society as a user of services. With a better understanding of the duties and loyal responsibilities of office holders, it can improve the efficiency, competence, and quality of services provided to the community. This contributes positively in increasing public satisfaction with public services provided by the head of society as a user of services.